Differences in Attributions for Public and Private Face-to-face and Cyber Victimization Among Adolescents in China, Cyprus, the Czech Republic, India, Japan, and the United States. Issue 1 (2nd January 2017) - Wright, Michelle F.; Yanagida, Takuya; Aoyama, Ikuko; Dědková, Lenka; Li, Zheng; Kamble, Shanmukh V.; Bayraktar, Fatih; Ševčíková, Anna; Soudi, Shruti; Macháčková, Hana; Lei, Li; Shu, Chang
ABSTRACT: The authors' aim was to investigate gender and cultural differences in the attributions used to determine causality for hypothetical public and private face-to-face and cyber victimization scenarios among 3, 432 adolescents (age range = 11–15 years; 49% girls) from China, Cyprus, the Czech Republic, India, Japan, and the United States, while accounting for their individualism and collectivism. Adolescents completed a questionnaire on cultural values and read four hypothetical victimization scenarios, including public face-to-face victimization, public cyber victimization, private face-to-face victimization, and private cyber victimization. After reading the scenarios, they rated different attributions (i.e., self-blame, aggressor-blame, joking, normative, conflict) according to how strongly they believed the attributions explained why victimization occurred. Overall, adolescents reported that they would utilize the attributions of self-blame, aggressor-blame, and normative more for public forms of victimization and face-to-face victimization than for private forms of victimization and cyber victimization. Differences were found according to gender and country of origin as well. Such findings underscore the importance of delineating between different forms of victimization when examining adolescents' attributions.